'No true or just test of merit': 'The Public School Record' 1886–1900. Issue 5 (3rd September 2022) - Carter, Andy
ABSTRACT: 'School league tables' summarising the performance of secondary schools in England have been published annually since 1992. Although now a firmly established feature of the educational landscape, they have attracted criticism from those who point to their unintended negative consequences. These include 'teaching to the test', entering pupils for easier examinations, and resitting examinations multiple times in order to massage success rates. However, neither the concept of league tables, nor these alleged side-effects are new. Between 1886 and 1900, a series of London newspapers published rudimentary tables that attempted to rank and compare schools based on performance. Initially conceived as an exercise in investigating whether leading public schools really provided educational value, and against a background of political conflict over elite classical education, they provoked intense debate over how to judge the quality of secondary education in late Victorian Britain. This paper examines their short history.